Risk Factors and Clinical Outcomes for Patients With Acinetobacter baumannii Bacteremia. Issue 9 (March 2016) - Gu, Zhenyang; Han, Yuliang; Meng, Taojiang; Zhao, Shasha; Zhao, Xiaoli; Gao, Chunji; Huang, Wenrong
Abstract : Abstract: Acinetobacter (A.) baumannii, an opportunistic nosocomial pathogen that can cause significant morbidity and mortality, has emerged as a worldwide problem. This study aimed to analyze the clinical features and outcomes of patients with A. baumannii bacteremia and determine the factors influencing survival by using 14-day mortality as the primary endpoint. A 6-year retrospective study of 122 cases with monomicrobial A. baumannii bacteremia was conducted in Chinese People's Liberation Army (PLA) General Hospital from January 2008 to April 2014. Predictors of 14-day mortality were identified by logistic regression analysis. The overall 14-day mortality rate was 40.2% (49 of 122 patients). Multivariable analysis revealed that independent predictors of 14-day mortality included severity of illness defined by Pitt Bacteremia Score (PBS) (odds ratio [OR], 0.46; 95% confidence interval [CI], 0.340–0.619; P < 0.001), neutropenia (OR, 18.02; 95% CI, 1.667–194.67; P = 0.017), and malignancy (OR, 4.63; 95% CI, 1.292–16.588; P = 0.019). The effect of malignancy was influenced by neutropenia (OR for interaction term, 1.60; 95% CI, 1.15–2.22; P = 0.005). A subgroup analysis revealed that 14-day mortality rate for patients with underlying hematological malignancies and solid tumors was 75% (12/16) and 40% (12/30), respectively. Survival analysis revealed that mortality in patients with hematological malignancies was higher than that in patients with solid tumors ( P = 0.032). The outcomes of patients with A. baumannii bacteremia were related to PBS, neutropenia, and malignancy. Compared with solid tumors, patients with hematological malignancies had a higher mortality in the setting of A. baumannii bacteremia.